Engineering Identities, Epistemologies and Values
XXXIV, 416 p. 18 illus.
Keywords: This second companion volume on engineering studies considers engineering practice including contextual analyses of engineering identity, epistemologies, and values. Key overlapping questions examine such issues as an engineering identity, engineering self-understandings enacted in the professional world, distinctive characters of engineering knowledge, and how engineering science and engineering design interact in practice. Authors bring with them perspectives from their institutional homes in Europe, North America, Australia, and Asia. The volume includes 24 contributions by more than 30 authors from engineering, the social sciences, and the humanities. Additional issues the chapters scrutinize include prominent norms of engineering, how they interact with the values of efficiency or environmental sustainability. A concluding set of articles considers the meaning of context more generally by asking if engineers create their own contexts or are they created by contexts. Taken as a whole, this collection of original scholarly work is unique in its broad, multidisciplinary consideration of the changing character of engineering practice.